Cecil Ash interviewed by Rob Willis for the Rob and Olya Willis folklore collection - Ash, Cecil, 1924-; Willis, Rob, 1944-; Cameron, Bruce, 1953- (2002)
Folkloric recording.
Cecil Ash, a retired bookkeeper talks about his life and interest in vaudeville theatre, has been visually impaired since an early age. He recalls his working life throughout rural Australia and his interest in the Vaudeville era in Australia, attending many of the shows in Sydney. Cec now entertains at various charity functions and he records some of the comedy routines he performs. Ash talks about the Les Schipp show, sketches, patter (ie comedy routines), theatrical garb, fire eaters, tightrope walkers; money earner for entertainers during the Depression; the Marina Theatre in Mascot, N.S.W.; Tivoli theatre; vaudeville performers; getting involved in performing when his sight deteriorated; package shows for the Royal Blind Society in a concert party playing ukelele; performing vaudeville material in nursing homes.
Recitation: examples of joke patter, several one liners (unidentified) -- That's good, that's good, that's good (joke patter) -- Singing: fragment of a Tex Morton song -- Recitation: Wilf Carter parody The yodelling braille writer -- fragment of Bellbirds (Henry Kendall) -- Singing: Max Miller song (unidentified) -- Recitation: series of one liners.
Recorded with Bruce Cameron.
Recorded on Aug. 8, 2002 at Gosford, N.S.W.
Also available online
Timed summary (3 p.)
Keywords: Ash, Cecil, -- 1924- -- Interviews; Comedians with disabilities -- New South Wales -- Gosford -- Interviews; Vaudeville -- Australia -- Anecdotes; Theater -- Australia -- History -- Anecdotes